Non-suicidal self-injury: A bibliometrics study and visualization analysis from 2002 to 2022 - Dong, Xiangli; Zou, Yuchen; Zou, Qing; Zhao, Na; Li, Shilin; Liu, Guanxiu; Hu, Maorong; Sun, Weiming (Frontiers in Psychiatry, 2023)
Objective To overview the research actuality and offer the hotspots and cutting-edge issues in the field of Non-suicidal Self-injury (NSSI) by using bibliometric analysis. Materials and methods Publications related to NSSI from 2002 to 2022 were extracted from the Web of Science Core Collection (WoSCC) database. CiteSpace V 6.1.R2 and VOSviewer 1.6.18 were used to visually analyzed institutions, countries, journals, authors, references, and keywords in research on NSSI. Results A total of 799 studies about NSSI were analyzed via CiteSpace and VOSviewer. The number of annual publications related to NSSI is fluctuating growth. The USA and Harvard University are the most productive country and institutions. In the case of journals and co-cited journals, Psychiatry Research are the most productive journal and also ranked highest among co-cited journals. Furthermore, Michael Kaess has published the most publications, and Matthew K. Nock is the most cited author. An article published by Swannell SV et al. shows the highest citation counts. After analysis, the most common keywords are harm, adolescents and prevalence. The gender difference, diagnosis, and dysregulation are frontier areas of NSSI research. Conclusion This study analyzed the research of NSSI from multiple perspectives, and provides valuable information for researchers to capture the current status, hot spots, and frontier trends of NSSI.